Tourism Development and Promotion in Central Kalimantan Post Pandemi Covid-19: A Sustainable Economic Approach - Isra Misra (Garuda Prestasi Nusantara Consulting, 2023)
Tourism is one that is able to encourage the economic growth of a region. In various countries in Europe and America, tourism is a contributor to the increase in national income and foreign exchange of a country. In the data for 2020, after the COVID-19 pandemic outbreak, world tourist arrivals fell drastically by -80%. This study aims to describe the development and promotion of tourism with a sustainable economic approach by taking into account social and environmental aspects. This research is a research library where researchers obtain data based on secondary data and scientific references such as books, journals, notes and reports as well as statistical data. The approach taken is descriptive qualitative. The stages in the research consist of collecting library materials, making research notes, sorting data and drawing conclusions. The results show that the development of tourist areas in Central Kalimantan must be carried out with a social approach to the community that emphasizes local cultural customs and sustainable tourism. Development is a strategic step in increasing the interest of local and visiting foreign tourists. The development is carried out with a planning pattern that involves experts from both academics and tourism practitioners. Tourism development and promotion strategies are ways or efforts to increase interest and the number of tourist visits by developing tourist objects and other supports. Several strategies for developing and promoting tourism in Central Kalimantan after the COVID-19 pandemic include identifying targets, making policies, creating a tourism climate, designing promotional messages, selecting promotional channels, determining budgets, determining the promotion mix and evaluating promotions.